Investigating the Use of Indigenous Languages Within South African Schools to Teach Cyber-Safety Awareness - (:unkn) unknown (My University, 2024)
Language is an essential instrument for both learning and teaching, used extensively by educational institutions at all levels across the globe. In South Africa, the integration of languages in school systems has been an ongoing debate. In the digital age, where technology and online safety are crucial, ensuring that educational resources are accessible and understandable to all learners is important. However, the majority of South Africans engage in indigenous languages, raising concerns about the efficiency of cyber-safety awareness offered only in English or other non-indigenous languages. This study investigated the use of indigenous languages within South African schools to enhance cyber-safety awareness among learners and to explore teachers’ perspectives on their use of languages in the curriculum. A quantitative approach was employed for data collected through a survey questionnaire administered to 150 teachers in selected schools in the Ekurhuleni district of Gauteng, South Africa. Based on holistic result analysis using SPSS software, the results show that teachers require training in the integration of indigenous languages for cyber-safety awareness in the classroom. Additionally, the integration of indigenous languages can enhance cyber-safety awareness among learners and boost cultural relevance in education. The findings contribute to the discourse on inclusive education and inform strategies for promoting cyber-safety awareness in multicultural settings.
Keywords: African Research